El péndulo patriótico : historia del Partido Nacionalista Vasco 1895-2005 / Santiago de Pablo, Ludger Mees, - Mees, Ludger; Pablo, Santiago de (1959-) (Crítica/Contrastes)
Bibliografía. Índices. Fuentes